PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN TOKO BANGUNAN DI SANGATTA-KUTAI TIMUR - Meita Sondang Rizki (Economic Faculty, University of Widya Gama Mahakam Samarinda, 2017)
The study tries to identify to what extent service quality for satisfaction of consumen store building in Sangatta. Analysis model used to prove hypothesis is model analysis multiple linier regression that be analysed with using statistics computer program package, that is SPSS v. 20.0 for Windows. Furthermore it was conducted examination for validity of data by multikolinieritas test, heteroskedastisitas test and autocorrelation test. Result of statistics analysis show that coefficient of the free variables regression, that is involvement factor in tangibles (X1) = 0,161, reliability (X2) = 0,088, responsiveness (X3) = 0,168, assurance (X4) = 0,194, emphaty (X5) = 0,122 and constanta equal to 0,541. Equation of multiple linier regression is: Y = 0,541 + 0,161 X1 + 0,088 X2 + 0,168 X3 + 0,194 X4 + 0,122 X5 + e Conclusion that receive that level of influence explained by tangibles, reliability, responsiveness, assurance, emphaty are as independent variable impact toward satisfaction of consumen store building equal to correlation coefficient (R), that is 0,860 and level of depended performance to second of free variables above is equal to determination coefficient value (R2) that is 0,740 or 74,0 %. Result of analysis F – test indicate that all free variables by together have significant influence toward satisfaction of consumen store building in Sangatta. By partial, variable tangibles, responsiveness, assurance, emphaty have significant influence to satisfaction of consumen store building in Sangatta. Variabel independent has dominant influence to satisfaction of consumen store is tangibles.